PENGARUH PARTISIPASI ANGGARAN, KEJELASAN TUJUAN ANGGARAN, DAN EVALUASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH ( Studi Empiris pada Satuan Kerja Pemerintah Daerah (SKPD) Kota Banda Aceh ) - Jalaluddin Jalaluddin; Dafi Bahri (Jurnal Telaah dan Riset Akuntansi, 2009)
The purpose of this research is to be able to test and analyze the effects of budget participation,clarity of budget goals, and evaluation of budget performance regional government officials in Banda Aceh city. Population in this research is that local government officials which amounted to 35 institutions 1 Secretariat area, 12 offices, 16 Service, Hospital 1, and 5 Agency. While the sample in this study consisted of, Chief Secretary / Department / Agency / Hospital / and the Office, the Head of Planning, and Ka.TU participated in thepreparation of theBudget.The collection of data and information needed in the study conducted by research field (field research). The primary data obtained  directly from research subjects in the form of perceptions by responden of the quetsionneir circulated in the form of a quitsionnaire  to 93 respondents.The study found that budget participation, clarity of budget goals, and evaluation of budgets simultaneously either partially or significantly affect the performance of local government officials in Banda Aceh city government. This shows that that in the formulation, implementation, and budget accountability has to follow the established rules of the staff and community participation in both formulating, implementation, and budget accountability has to follow the established rules of the staff and community participation in both formulating, implementing, and budget accountability. Qualitative research paper supports the findings of quantitative analysis.To strengthen subsequent research needs to be testing again to see the consistency of previous studies. In order for the next studies need to be more representative or the addition of the addition or substitution of variables for supporting the research findings better or more extensive. Keyword: Budget Participation, Goal Clarity Budget, Budget and Performance Evaluation